Analyzing the Determinants of BNPL Users Among Young People in West Sumatera: A Logistic Regression Approach - Nisa, Fachrum; Fany Alfarisi, Mohamad; Hamidi, Masyhuri (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the factors influencing the use of Buy Now, Pay Later (BNPL) services among the youth in West Sumatra using a logistic regression approach. The factors tested include socio-economic characteristics (gender, education level, and income), BNPL promotions, social influence, and financial self-control. Data were collected through a survey with a sample of 200 respondents consisting of millennials and Generation Z in the area. The findings demonstrate that BNPL promotion and social influence significantly and positively affect BNPL adoption, while gender, education, income, and financial self-control show no significant impact. These findings provide the importance of effective and responsible marketing strategies and social validation in driving BNPL usage. This study also recommends strengthening regulations to enhance consumer protection in the technology-based financial services ecosystem.